The Effectiveness of Group Guidance with Modeling Techniques on Student Learning Independence - Nafisha, Jihanda; Arsini, Yenti (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to determine the effectiveness of group guidance with modeling techniques in increasing student learning independence. This quantitative research with a one-group pre-test-post-test pre-experimental design aims to determine the effectiveness of group guidance with modeling techniques in improving the learning independence of students in grade XI MAS Plus Al-Ulum Medan. Data was obtained from a learning independence questionnaire, with a sample of 12 students selected using the purposive sampling technique. The data collection technique was carried out through pre-test and post-test, which was then analyzed using the Wilcoxon test. The results showed that group guidance with modeling techniques was effective in increasing students' learning independence, with a significance value of 0.002. This increase can be seen from the average pre-test score of 73.58 (low-medium) to 98.83 (medium-high) in the post-test. It is proven that group guidance with modeling techniques is an effective method to increase student learning independence.